The value of small-scale student projects in undergraduate research training - Sanet du Toit; Annette Wilkinson (Acta Academica, 2010)
This article reports on the undertaking of small-scale projects for final-year Occupational Therapy (OT) students training at the University of the Free State. An Action Learning Action Research (ALAR) approach was used to investigate the impact of such projects in a clinical setting. A tree analogy is used to describe the student projects, providing the body of the investigation as a whole, and sharing the experience gained in determining the constituents of the “fertile soil” and conditions for “optimum growth”. The impact of ALAR on practical experience is explained as a first step towards establishing a research culture among undergraduate students in OT as well as in similar training contexts.